2017
DOI: 10.17501/icoph.2017.3103
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Perceived Stigma Towards Tuberculosis and the Implementation of Diagnosis Procedure on Tuberculosis Screening Program in Denpasar, Bali, Indonesia

Abstract: Abstract:The major issue of Tuberculosis (TB) control program in Indonesia including Bali is the low cases detection rate (32%). An intensive presumptive TB finding through screening program and then followed by diagnosis procedure is important to conduct. Meanwhile, perceived stigma is a social determinant of health that strongly associated to health-seeking behaviour. This study aimed to assess the association of perceived stigma towards TB to diagnosis procedure implementation among presumptive TB casesscre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…However, the proportion of PGPs who referred the suspected TB patients in both studies were quite high, 92.73% in our study and 81.10% in Denpasar. 12 Our finding is lower when compared to a study in Jogyakarta in 2004 which identified as many as 63.40% of PGPs found suspected TB patients in the last year, but the proportion of PGPs who referred suspected TB patients is similar. 13 The different proportion of PGPs who found suspected TB patients in the two studies may related to TB prevalence and local health systems.…”
Section: Tb Knowledge N (%)contrasting
confidence: 89%
See 1 more Smart Citation
“…However, the proportion of PGPs who referred the suspected TB patients in both studies were quite high, 92.73% in our study and 81.10% in Denpasar. 12 Our finding is lower when compared to a study in Jogyakarta in 2004 which identified as many as 63.40% of PGPs found suspected TB patients in the last year, but the proportion of PGPs who referred suspected TB patients is similar. 13 The different proportion of PGPs who found suspected TB patients in the two studies may related to TB prevalence and local health systems.…”
Section: Tb Knowledge N (%)contrasting
confidence: 89%
“…system by providing credit points for PGPs who participated in TB control programs. 12 Our study also found that supervision by TB officials is associated with participation to refer suspected TB patients, even though the supervision is inadequate. Supervision in Badung District is conducted by TB officials from public health centres only once, and supervision by district and provincial health office only done to two PGPs per three months.…”
Section: Tb Knowledge N (%)mentioning
confidence: 50%